Evaluating the Role of Point-of-Care Lactate Measurement in Predicting Severity and Outcomes of Diabetic Ketoacidosis in Emergency Settings: Point-of-Care Lactate for Predicting Severity and Outcomes in Diabetic Ketoacidosis - Manzoor, Imtiaz; Dass, Rajesh Jamna; Aman, Faryal; Ilyas, Sana; Zaib, Faiza; Anwar, Sidra (Pakistan Journal of Health Sciences, 2026)
Diabetic ketoacidosis is one of the severe diabetic emergencies with hyperglycaemia, acidosis, and ketonemia, and an increased level of lactate is an indicative feature of metabolic stress and unfavourable prognosis, necessitating urgent assessment and immediate care. Objectives: To assess the frequency of elevated point-of-care lactate in patients presenting with diabetic ketoacidosis (DKA) and to evaluate its association with DKA severity and in-hospital mortality. Methods: Data were prospectively collected from patients after obtaining verbal consent. Both quantitative and qualitative data were collected and analysed using SPSS version 23.0. Chi-square tests were applied, with a p-value of ≤0.05 considered significant. The study employed a descriptive cross-sectional design, conducted over six months (January 7, 2023, to June 7, 2023) at the Department of Medicine, Civil Hospital, Karachi. Results: A total of 131 patients were included, with a mean age and duration of T2DM of 47.14 ± 16.49 years and 1.72 ± 1.24 years, respectively. Among the participants, 71 (54.2%) were male, and 60 (45.8%) were female. Out of 131 patients, 64 (48.9%) had elevated point-of-care lactate, while 67 (51.1%) did not. In-hospital mortality occurred in 14 (60.9%) patients with elevated point-of-care lactate. The majority of patients presented with moderate DKA. Conclusions: The findings conclude that initial lactate levels in DKA patients are significantly associated with the need for critical care, suggesting that lactate can be used as a reliable marker for monitoring and managing DKA patients.